Challenges in treating patients with inflammatory bowel disease and concurrent viral hepatitis infection. (1st December 2016) - Degasperi, Elisabetta; Caprioli, Flavio; El Sherif, Omar; Back, David; Colombo, Massimo; Aghemo, Alessio
ABSTRACT: Introduction : Inflammatory bowel diseases (IBD) require long-term administration of immunomodulatory treatments to maintain disease remission. Due to the high worldwide prevalence of hepatitis B (HBV) or C (HCV) virus infections, presence of concurrent hepatitis can be a relevant clinical issue to manage when treating IBD. Areas covered : The paper summarizes epidemiological data about IBD and HBV/HCV infection and reviews current knowledge about the natural history of HBV and HCV in the IBD setting, concentrating on risk of hepatitis reactivation during immunosuppressive treatment. Most updated recommendations for management of HBV and HCV infections in IBD patients are discussed. Expert commentary : The development of new drugs for IBD with different molecular targets and the availability of potent and efficacious antiviral drugs for HBV and HCV will simplify management of hepatitis infection in IBD patients in the near future.